THE ENYIRONMENTAL KUZNETS CURVE IN TRANSITION COUNTRIES ON THE EXAMPLE OF POLAND - BERNACIAK, Arnold (Economic and Environmental Studies, 2021)
This study of the welfare-environmental pressure relationship in a transition economy covered only chosen indicators. Some of them seem to confirm the EKC hypothesis, others do not give any evidence for it.